Overview of online learning in business education - Coleman, Maébh (Henry Stewart Talks, 2019)
Online learning, Business education, Accreditation & value addition, A brief history of online learning, Technology adoption, The adoption curve, Lifecycles of technologies, Examples from higher education & industry